Genealogie - Markewitz, Friedrich (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik)

Gouvernementalität - Markewitz, Friedrich (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik)

Dispositiv - Markewitz, Friedrich (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik)

Archäologie - Markewitz, Friedrich (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik)

Fachtextsorte - Markewitz, Friedrich (Fachtextsorte)

Gebrauchstextsorte - Markewitz, Friedrich (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik)

Trade and economic development: global causality and development- and openness-related heterogeneity - Gries, Thomas; Redlin, Margarete (International Economics and Economic Policy)

Digitalisierung in der Lehrerbildung durch Communities of Practice. Konzeption, Governance und Qualitätsmanagement des ComeIn-Verbundvorhabens in Nordrhein-Westfalen - van Ackeren, Isabell; Buhl, Heike M.; Eickelmann, Birgit; Heinrich, Martin; Wolfswinkler, Günther (Bildung, Schule und Digitalisierung)

Intergenerational Value Similarity in Adulthood - Hoellger, Christian; Sommer, Sabrina; Albert, Isabelle; Buhl, Heike M. (Journal of Family Issues)
This investigation concentrates on value similarity between parents and their children during adulthood. The interplay between gender, age, relationship quality, and frequency of contact on value similarity was analyzed. A total of 600 adult German children (53.8% women) and their parents took part in a questionnaire study. Value orientation was measured with a short version of Schwartz’s Portrait Values Questionnaire, and relationship quality with the Network of Relationships Inventory (Furman & Buhrmeister, 1992).Value similarity was higher in mother–daughter dyads compared to mother–son dyads, but in the other dyads, no significant differences were found. Regarding relationship quality, verbal intimacy was not related to value similarity. Parental satisfaction was associated with value similarity in the father–child dyads. Satisfaction, as perceived by adult children, was linked to value similarity in mother–child and father–son dyads. Furthermore, the frequency of contact related to value similarity between mothers and sons.
Keywords: Adult child–parent dyads; value similarity; relationship quality; frequency of contact; parent-child-relationship

Urbane Kulturen und Räume intermedial. Zur Lesbarkeit der Stadt in interdisziplinärer Perspektive

On the experimental study of condensation in pillow plate heat exchangers - Buckmann, Felix; Kenig, Eugeny

Inverse piezoelectric material parameter characterization using a single disc-shaped specimen - Feldmann, Nadine; Schulze, Veronika; Claes, Leander; Jurgelucks, Benjamin; Walther, Andrea; Henning, Bernd (tm - Technisches Messen)
The increasingly simulation-driven design process of ultrasonic transducers requires several reliable parameters for the description of the material behaviour. Exact results can only be achieved when a single specimen is used in the identification process, which typically is prone to the problem of low sensitivities to certain material parameters and thus high uncertainties. Therefore, a custom electrode topology for increased sensitivity is proposed for a piezoceramic disc. The thereupon conducted measurements of the electric impedance can be used as a starting point for an inverse approach where an equivalent simulation model is used to identify fitting material parameters. An optimisation strategy based on a preliminary sensitivity analysis is presented that leads to a good agreement between measurement and simulation. Furthermore, the proposed measurement procedure is able to evaluate the quality of the simulation model. Hence, different frequency-dependent damping models are presented and evaluated.

Linear Algebra driven by Data Science - Schramm, Thomas; Gasser, Ingenuin; Schwenker, Sören; Seiler, Ruedi; Lohse, Alexander; Zobel, Kay
Dieses Lernangebot widmet sich der linearen Algebra als dem Teil der Mathematik, der neben der Optimierung und der Stochastik die Grundlage für praktisch alle Entwicklungen im Bereich Künstliche Intelligenz (KI) darstellt. Das Fach ist jedoch für Anfänger meist ungewohnt abstrakt und wird daher oft als besonders schwierig und unanschaulich empfunden. In diesem Kurs wird das Erlernen mathematischer Kenntnisse in linearer Algebra verknüpft mit dem aktuellen und faszinierenden Anwendungsfeld der künstlichen neuronalen Netze (KNN). Daraus ergeben sich in natürlicher Weise Anwendungsbeispiele, an denen die wesentlichen Konzepte der linearen Algebra erklärt werden können. Behandelte Themen sind: Der Vektorraum der reellen Zahlentupel, reelle Vektorräume allgemein Lineare Abbildungen Matrizen Koordinaten und darstellende Matrizen Lineare Gleichungssysteme, Gaußalgorithmus Determinante Ein Ausblick auf nichtlineare Techniken, die für neuronale Netzwerke relevant sind.

Generalised Symmetry in Network Dynamics - Nijholt, Eddie; Rink, Bob; Schwenker, Sören (DSWeb)

A new algorithm for computing idempotents of ℛ-trivial monoids - Nijholt, Eddie; Rink, Bob; Schwenker, Sören (Journal of Algebra and Its Applications)
The authors of Berg et al. [J. Algebra 348 (2011) 446–461] provide an algorithm for finding a complete system of primitive orthogonal idempotents for CM, where M is any finite R-trivial monoid. Their method relies on a technical result stating that R-trivial monoid are equivalent to so-called weakly ordered monoids. We provide an alternative algorithm, based only on the simple observation that an R-trivial monoid may be realized by upper triangular matrices. This approach is inspired by results in the field of coupled cell network dynamical systems, where L-trivial monoids (the opposite notion) correspond to so-called feed-forward networks. We first show that our algorithm works for ZM, after which we prove that it also works for RM where R is an arbitrary ring with a known complete system of primitive orthogonal idempotents. In particular, our algorithm works if R is any field. In this respect our result constitutes a considerable generalization of the results in Berg et al. [J. Algebra 348 (2011) 446–461]. Moreover, the system of idempotents for RM is obtained from the one our algorithm yields for ZM in a straightforward manner. In other words, for any finite R-trivial monoid M our algorithm only has to be performed for ZM, after which a system of idempotents follows for any ring with a given system of idempotents.
Keywords: Applied Mathematics; Algebra and Number Theory

Quiver Representations and Dimension Reduction in Dynamical Systems - Nijholt, Eddie; Rink, Bob W.; Schwenker, Sören (SIAM Journal on Applied Dynamical Systems)
Dynamical systems often admit geometric properties that must be taken into account when studying their behavior. We show that many such properties can be encoded by means of quiver representations. These properties include classical symmetry, hidden symmetry, and feedforward structure, as well as subnetwork and quotient relations in network dynamical systems. A quiver equivariant dynamical system consists of a collection of dynamical systems with maps between them that send solutions to solutions. We prove that such quiver structures are preserved under Lyapunov--Schmidt reduction, center manifold reduction, and normal form reduction.
Keywords: Modeling and Simulation; Analysis

A Characterization of the Finiteness of Perpetual Integrals of Levy Processes - Kolb, Martin; Savov, Mladen (Bernoulli)
We derive a criterium for the almost sure finiteness of perpetual integrals of L ́evy processes for a class of real functions including all continuous functions and for general one- dimensional L ́evy processes that drifts to plus infinity. This generalizes previous work of D ̈oring and Kyprianou, who considered L ́evy processes having a local time, leaving the general case as an open problem. It turns out, that the criterium in the general situation simplifies significantly in the situation, where the process has a local time, but we also demonstrate that in general our cri- terium can not be reduced. This answers an open problem posed in D ̈oring, L. and Kyprianou, A. (2015).
Keywords: L ́evy processes; Perpetual integrals; Potential measures

Wahrheit, Freiheit, Demokratie – Zum Umgang mit Hochwertausdrücken in rechtspopulistischen bzw. neurechten Argumentationen anhand des Blogs „Politically Incorrect“ - Markewitz, Friedrich (Türkisch-Deutsche Studien Jahrbuch 2019:Migration movements and right-wing populism after 2015)

Generalized transitivity: A systematic comparison of concepts with an application to preferences in the Babington Smith model - Haddenhorst, Björn; Hüllermeier, Eyke; Kolb, Martin (International Journal of Approximate Reasoning)
Reciprocal relations are binary relations Q with entries Q(i,j)∈[0,1], and such that Q(i,j)+Q(j,i)=1. Relations of this kind occur quite naturally in various domains, such as preference modeling and preference learning. For example, Q(i,j) could be the fraction of voters in a population who prefer candidate i to candidate j. In the literature, various attempts have been made at generalizing the notion of transitivity to reciprocal relations. In this paper, we compare three important frameworks of generalized transitivity: g-stochastic transitivity, T-transitivity, and cycle-transitivity. To this end, we introduce E-transitivity as an even more general notion. We also use this framework to extend an existing hierarchy of different types of transitivity. As an illustration, we study transitivity properties of probabilities of pairwise preferences, which are induced as marginals of an underlying probability distribution on rankings (strict total orders) of a set of alternatives. In particular, we analyze the interesting case of the so-called Babington Smith model, a parametric family of distributions of that kind.

Auswirkungen der Digitalisierung industrieller Arbeit auf die allgemeine und berufliche Bildung - Berisha-Gawlowski, Angelina; Caruso, Carina; Goller, Michael; Harteis, Christian (Digitalisierung und Berufsbildung 4.0 am Übergang Schule - Beruf)